Law and Development Review (De Gruyter, 2008)
The Law and Development Review (LDR) - in cooperation with the Law and Development Institute - puts its primary focus on the development aspects of international and domestic legal orders. It helps exchange views globally on this important subject, particularly on the gap between the developed and developing worlds. The LDR seeks top-quality articles on law and development issues broadly.